2008
DOI: 10.3201/eid1412.080482
|View full text |Cite
|
Sign up to set email alerts
|

MultipleFrancisella tularensisSubspecies and Clades, Tularemia Outbreak, Utah

Abstract: In July 2007, a deer fl y-associated outbreak of tularemia occurred in Utah. Human infections were caused by 2 clades (A1 and A2) of Francisella tularensis subsp. tularensis. Lagomorph carcasses from the area yielded evidence of infection with A1 and A2, as well as F. tularensis subsp. holarctica. These fi ndings indicate that multiple subspecies and clades can cause disease in a localized outbreak of tularemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Ft subspecies holarctica is found throughout the Northern hemisphere, whereas Ft subspecies tularensis is restricted to North America. Recently, type A strains of Ft were divided into 2 clades; A1 strains are located in central and eastern United States, and A2 strains are more abundant than A1 strains in the west [21,56]. Moreover, for reasons that are as-yet unclear, the casefatality rate for humans infected with A1 strains is much higher (24%) than type B (7%) or A2 (0%) isolates [57].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ft subspecies holarctica is found throughout the Northern hemisphere, whereas Ft subspecies tularensis is restricted to North America. Recently, type A strains of Ft were divided into 2 clades; A1 strains are located in central and eastern United States, and A2 strains are more abundant than A1 strains in the west [21,56]. Moreover, for reasons that are as-yet unclear, the casefatality rate for humans infected with A1 strains is much higher (24%) than type B (7%) or A2 (0%) isolates [57].…”
Section: Discussionmentioning
confidence: 97%
“…The highly virulent subclone Schu S4 was isolated in 1951 and has since been studied widely [20]. Schu S4 and the Massachusetts strain (MA00-2987) belong to clade A1 [23], the Wyoming strain (WY96-3418) belongs to clade A2 [21,23], and isolates from 2 patients in Iowa are type B (1547-57 and 1623-36) [24]. TI0902 is a type A strain of an unknown subtype that was isolated from a cat [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Type B infections have been reported across the United States, but A1 and A2 clades are typically conÞned to east or west of the Rocky Mountains, respectively, with some geographic overlap in California (Farlow et al 2005, Staples et al 2006. A recent study demonstrated that A1 strains also occur in the intermountain west and that at very local scales, A1, A2, and type B infections can circulate in the same local epizootic (Petersen et al 2008).…”
mentioning
confidence: 94%
“…Indeed, in a tularemia outbreak in 2007 in North-Central Utah, a region predicted by the models, A1 strains were identified as the cause of the infections. 17 Similarly, a tularemia epizootic in lagomorphs caused by A2 strains occurred in Presidio, Jeff Davis, and Potter counties in Texas in 2006 (Centers for Disease Control, unpublished data), regions predicted by the models, but for which isolates were not included in the data set on which the models were based. Finally, although type B isolates from Michigan, Minnesota, and North Dakota were not included in the data set, the model strongly predicted distribution of type B in these areas; indeed, both human and animal infections caused by type B have previously been documented from these regions of the upper Midwest.…”
Section: Discussionmentioning
confidence: 99%